PEMBERIAN ZAT PENGATUR TUMBUH AUKSIN DENGAN BERBAGAI KONSENTRASI PADA BIBIT KARET (Hevea brasiliensis) STUM MATA TIDUR KLON PB 260 - Alfiansyah '; Sukemi Indra Saputra; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aimed to find out the influence on giving auksin plant growth regulator with various concentrations and to obtain the best concentration for the growth of budded rubber stum. This research was conducted at experimental farm of Farming Faculty of Riau University at Bina Widya st Km 12,5, Simpang Baru, Tampan, Pekanbaru. This research was carried out experimentally with Complete Random Design (CRD), the treatments given were the auksin plant growth regulator concentration which consisted of several stages (P0) without giving auksin plant growth regulator, (P1) concentration of 25 mg/0,5 ml water, (P2) concentration of 50 mg/ 0,5 ml water, (P3) concentration of 75 mg/ 0,5 ml water. Every treatment consisted of 5 repetition so that it was obtained 20 experiment units. Every experiment unit consisted of 3 plants and 2 plants were being sample. The observed parameters were that the time of buds emerging, the amount of leaves, the diameter of buds and the wide of buds. The obtained data was analyzed statistically with analysis of varience and continued to Duncan’s New Multiple Range Test (DNMRT) at 5% degree. The concentration of plant growth regulator 50 mg/0,5 ml water had the best effect for the growth of giving budded rubber stum (Hevea brasiliensis) clone PB 260. Keywords: Rubber plant, budded rubber stum, auksin plant growth regulator